PENYELESAIAN SENGKETA TRANSAKSI ELEKTRONIK - Gunawan Widjaja; Anastasia Prestika; Olivia Pauline Hartanti; Achmad Fazrin (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2018)
In Electronic Transactions dispute resolution can be carried out through the courts (Class action and Civil Lawsuits) or non-litigation settlements (Mediation, Negotiation, and Arbitration).